The Influence of Foreign Exchange Reserves, GDP per Capita, Exchange Rate, Degree of Openness, Budget Deficit, and Current Account Balance on Indonesia’s External Debt during the Period 1990–2023 - Haura, Regina Alya; Utomo, Yuni Prihadi (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the influence of Foreign Exchange Reserves, Gross Domestic Product per Capita, Exchange Rate, Degree of Openness, Fiscal Deficit, and Current Account Balance on Indonesia’s External Debt during the period 1990–2023. This study employs a quantitative research approach using time series data. The data analysis technique applied is Ordinary Least Squares (OLS) regression. The research results indicate that the exchange rate has a significant positive effect on external debt. This suggests that a weakening rupiah leads to an increase in external debt because the repayment burden is dominated by foreign currency. Conversely, the budget deficit and current account balance have a significant negative effect on external debt. This implies that when a fiscal deficit occurs, external financing is required to cover the deficit, which in turn will increase external debt. Meanwhile, Foreign Exchange Reserves, Gross Domestic Product per Capita, and Degree of Openness are found to have no significant effect on External Debt. This indicates that during this period, the three variables did not have a direct role in determining fluctuations in External Debt. Indonesia’s external debt remains a structural issue influenced by the depreciation of the rupiah, fiscal deficits, and a weak current account balance. Dependence on external financing increases the risk of debt burdens, particularly when the rupiah depreciates. The government needs to strengthen exchange rate stability, enhance domestic revenue, and improve the current account balance through export promotion and import control. Debt management should be productive, transparent, and accountable to ensure sustainable economic development and fiscal stability.